The importance of indigenous peoples’ lands for the conservation of terrestrial mammals - O’Bryan, C.J.; Garnett, S.T.; Fa, J.E.; Leiper, I.; Rehbein, J.; Fernández‐Llamazares, Á.; Jackson, M.V.; Jonas, H.D.; Brondizio, E.S.; Burgess, Neil D.; Robinson, C.J.; Zander, K.K.; et al. (Wiley, 2021)
Indigenous Peoples’ lands cover over one‐quarter of Earth's surface, a significant proportion of which is still free from industrial‐level human impacts. As a result, Indigenous Peoples and their lands are crucial for the long‐term persistence of Earth's biodiversity and ecosystem services. Yet, information on species composition on these lands globally remains largely unknown. We conducted the first comprehensive analysis of terrestrial mammal composition across mapped Indigenous lands based on data on area of habitat (AOH) for 4460 mammal species assessed by the International Union for Conservation of Nature. We overlaid each species’ AOH on a current map of Indigenous lands and found that 2695 species (60% of assessed mammals) had ≥10% of their ranges on Indigenous Peoples’ lands and 1009 species (23%) had >50% of their ranges on these lands. For threatened species, 473 (47%) occurred on Indigenous lands with 26% having >50% of their habitat on these lands. We also found that 935 mammal species (131 categorized as threatened) had ≥ 10% of their range on Indigenous Peoples’ lands that had low human pressure. Our results show how important Indigenous Peoples’ lands are to the successful implementation of conservation and sustainable development agendas worldwide.